Manfaat Olahraga Pada Usia Lanjut - hayati, Hayati (Program Studi S1 Kebidanan - Fakultas Sains dan Kesehatan Universitas PGRI Adi Buana Surabaya, 2013)
In development and advanced country the expectation age have been increased. This increased connected with the big decreased in prevalence of the cardiovascular disease and stroke.In elderly in which the physical fitness have been decreased, training with low intensity ( for example 40% of maximal heart rate ) will be more safe and can increased the physical and mental fitness that can make them not depend to another people. In elderly the decline of body function 50% was caused by the sedentary life. The consequency of immobilization influenced body systems such as cardiovascular, respiration, body composition and musculoskeletal, nervous system and also the senses and intellectual. Training indirectly can make elder have social interaction, feeling well and increased sleeping quality. Directly training can increased the body function, prevent and cure some diseases. The training program for elder include theurapetic training, muscle and strength training, balance training and stretching.